1987
DOI: 10.5547/issn0195-6574-ej-vol8-no1-7
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of the Market for Energy Efficiency in Residential Appliances Including Heating and Cooling Equipment

Abstract: Our paper provides a quantitative analysis of market behavior for the purchase of energy efficiency in residential appliances and heating and cooling equipment. Accurate forecasts of residential energy use require quantitative assessments of market decisions about energy efficiency. The results of our investigation of market behavior can lead to a better understanding of the barriers to investment in energy conservation. Understanding market behavior over time is a prerequisite to an evaluation of the need for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(73 citation statements)
references
References 4 publications
0
73
0
Order By: Relevance
“…A large body of research demonstrates that purchasers appear to use relatively high discount rates in evaluating energy-efficiency investments (Hausman, 1979;Ross, 1990;Ruderman et al, 1987). The implicit or explicit use of relatively high discount rates for energy savings does not represent a market failure in itself; it is rather the manifestation of underlying aspects of the decision process including those just discussed.…”
Section: Environmental Policy and Adoptionmentioning
confidence: 99%
“…A large body of research demonstrates that purchasers appear to use relatively high discount rates in evaluating energy-efficiency investments (Hausman, 1979;Ross, 1990;Ruderman et al, 1987). The implicit or explicit use of relatively high discount rates for energy savings does not represent a market failure in itself; it is rather the manifestation of underlying aspects of the decision process including those just discussed.…”
Section: Environmental Policy and Adoptionmentioning
confidence: 99%
“…Sanstad and Howarth (1994) present a similar survey, analyzing the theories around consumer rationality in energy efficiency choices. Other studies, like Ruderman et al (1987) have even revealed that the consumers can use excessive rates (as high as 88% per year) when making energy related decisions. Hausman (1979) has found a discount rate from 89% progressively reducing to 5.1% following an inverse order of household income levels.…”
Section: Article In Pressmentioning
confidence: 99%
“…Such a holistic "savings-oriented" approach might not be adopted by others, such as operations or facilities managers who might focus more on the technical feasibility of the recommendation. We therefore propose the following hypothesis: The literature has shown that managers apply high discount rates to the evaluation of energy efficiency investments (Ruderman et al, 1987;Ross, 1986;Howarth and Sanstad, 1995) and describe managers' preference for recommendations with rapid payback rather than long-term benefit (DeCanio, 1993;Sorrell et al, 2000). Here we argue that such preference might not be true for top managers as compared to other managers and employees.…”
Section: Hypothesesmentioning
confidence: 99%